Changes in microtubule-related proteins and autophagy in long-term vitamin E-deficient mice. (June 2014) - Fukui, K.; Masuda, A.; Hosono, A.; Suwabe, R.; Yamashita, K.; Shinkai, T.; Urano, S.
Abstract Vitamin E deficiency induces neuronal dysfunction and while oxidative stress is likely to be involved in mediating this process, the detailed mechanisms remain to be elucidated. Previously, we found axonal degeneration in the hippocampal CA1 region in vitamin E-deficient mice of 6 months of age (long-term). However, 3 month-old (short-term) vitamin E-deficient mice did not exhibit axonal degeneration in same region. In order to characterize the mechanisms involved in axonal degeneration in long-term vitamin E-deficient mice, we examined changes in microtubule-related proteins. Long-term vitamin E-deficiency led to significantly increased expression of the phosphorylated form of collapsin response mediator protein (CRMP)-2 compared to short-term deficiency. It is well known that CRMP-2 plays a crucial role in the maintenance of neurite function. Similarly, long-term vitamin E-deficiency significantly decreased the expression of silent mating type information regulation (SIRT)-2 mRNA compared to short-term deficiency. SIRT-2 belongs to a family of class III histone deacetylases (HDACs) and functions in the deacetylation of tubulins. Furthermore, the expression of microtubule-associated protein light chain (MAP-LC)3-2, which is a key autophagy protein was significantly higher in the short-term vitamin E-deficiency than the long-term deficiency. These results indicate that the mechanisms of axonal injury in long-term vitamin E-deficient mice are related to dysfunction in microtubules assembly via alterations in microtubule-related proteins and autophagy.